Создание контрольно-калибровочного полигона подспутниковой поддержки - Зелык, Я.И.; Яценко, В.А.; Набивач, В.Е.; Семенив, О.В.; Подгородецкая, Л.В. (Проблемы управления и информатики, 2013)
Космический мониторинг The problems of the optical satellite-born equipment post launch calibration using for the first time founded in Ukraine calibration test site (CTS) in the area of National Space Center are formulated and in the first stage solved. On the base of the synchronous satellite imagery with ground-based measurements results of the test object (TO) spectral reflectance characteristics the presentation catalog and geo informational database are created. Database includes the polygonal TO vector layers, «Quick Bird-2» and «Sich-2» satellite images, digital model of CTS territory. CTS infrastructure is defined and instruments with the PSC should be equipped as the number of available to researchers and the instruments used at LANDNET test sites of CEOS Committee are analyzed.